2022
DOI: 10.1007/s11274-022-03257-w
|View full text |Cite
|
Sign up to set email alerts
|

Basidiocarp structures of Lentinus crinitus: an antimicrobial source against foodborne pathogens and food spoilage microorganisms

Abstract: Lentinus crinitus basidiocarps are an alternative to antimicrobials, but the stipe (24% basidiocarp) is discarded even with potential antimicrobial activity. This study evaluated the antimicrobial activity of L. crinitus basidiocarp pileus and stipe extracts against foodborne pathogens and food spoilage microorganisms. Basidiocarps of L. crinitus were grown in sugarcane bagasse and rice husks and the pileus and stipe methanolic extract was analyzed by broth microdilution method for antimicrobial activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Further, extracts of L. crinitus showed high percentages of inhibition of E. coli, S. typhimurium, R. oryzae, F. oxysporum and A. niger. A more recent investigation evaluated the antimicrobial activity of L. crinitus basidiocarp, where the minimum bactericidal and fungicidal concentration values similar to or lower than those verified by commercial antibiotics or food additives used as preservatives [ 6 ] and other investigation show the L. crinitus basidiocarps are an alternative to antimicrobials against foodborne pathogens and food spoilage microorganisms [ 5 ]. There are no reports of aqueous extracts of L. crinitus obtained from the spent mushroom substrate obtained from solid fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, extracts of L. crinitus showed high percentages of inhibition of E. coli, S. typhimurium, R. oryzae, F. oxysporum and A. niger. A more recent investigation evaluated the antimicrobial activity of L. crinitus basidiocarp, where the minimum bactericidal and fungicidal concentration values similar to or lower than those verified by commercial antibiotics or food additives used as preservatives [ 6 ] and other investigation show the L. crinitus basidiocarps are an alternative to antimicrobials against foodborne pathogens and food spoilage microorganisms [ 5 ]. There are no reports of aqueous extracts of L. crinitus obtained from the spent mushroom substrate obtained from solid fermentation.…”
Section: Discussionmentioning
confidence: 99%
“… Brazil 2021 [ 69 ] Basidiocarp pileus and stipe/Solid State Fermentation Methanolic extracts Antimicrobial activity against Bacillus cereus, Enterobacter cloacae, Escherichia coli, Listeria monocytogenes, Micrococus luteus, Pseudomonas aeruginosa, Salmonella enterica, Staphylococcus aureus, Aspergillus fumigatus, Aspergillus niger, Aspergillus versicolor, Penicillium aurantiogriseum, Penicillium ochrochlonron, Talaromyces funiculosus and Trichoderma virens. Brazil 2021 [ 5 ] Mycelial biomass/Submerged Fermentation Methanolic extracts Antimicrobial activity against Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Escherichia coli, Salmonella enterica, Enterobacter cloacae, Aspergillus fumigatus, Aspergillus niger, Aspergillus versicolor, Talaromyces funiculosus, Penicillium aurantiogriseum and Trichoderma virens. Brazil 2022 [ 70 ] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are around 140,000 different types of mushrooms have been identified so far, and numerous studies have shown that they have antimicrobial and bioactive properties. Scientists have investigated the potential of edible mushrooms in the food industry (Berteli et al, 2022;Han et al, 2022). However, more studies are going to be conducted in this area because there are so few reports available mentioning the actual uses of mushroom anti-microbial as control agents for food safety.…”
Section: Mushroomsmentioning
confidence: 99%